THEORETICAL PHONETICS AS A SCIENCE - Khaydarova Nigora; Abdulkhamidova Shuhratoy (TADQIQOTLAR, 2025)
Abstract This article examines theoretical phonetics as a scientific discipline, its object of study, methods, and significance in linguistics. Theoretical phonetics investigates the sound system of language, revealing the laws that govern the production, transmission, and perception of speech sounds. As a science, it provides a systematic and theoretical basis for understanding spoken language.